1998
DOI: 10.1007/bf03012092
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin injection after Caesarean delivery: intravenous or intramyometrial?

Abstract: Purpose: To determine, after Caesarean delivery, uterine contractility and blood pressure following intravenous (iv) and intramyometrial (imy)injection of oxytocin. Methods: In a double-blind clinical trial 40 parturients scheduled for elective Caesarean section with spinal anaesthesia were randomized into two equal groups. One litre Ringer's lactate was administered iv before intrathecal injection of 1.7 ml bupivacaine 0.75% and 0.3 mg morphine. All patients received simultaneous iv and irny injections after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…The obstetrician was allowed to freely carry out a uterine massage. Uterine tone was assessed on a 10‐point linear analog scale (0 = floppy, 10 = maximum contraction) at 2, 4, 6, 8, 10, 15, and 20 min after the injection. Moreover, we defined SBP that decreased below 20% of the value at the time of uterine incision as hypotension.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The obstetrician was allowed to freely carry out a uterine massage. Uterine tone was assessed on a 10‐point linear analog scale (0 = floppy, 10 = maximum contraction) at 2, 4, 6, 8, 10, 15, and 20 min after the injection. Moreover, we defined SBP that decreased below 20% of the value at the time of uterine incision as hypotension.…”
Section: Methodsmentioning
confidence: 99%
“…group was 2.73 mmHg lower than that of the i.m.y. group (β error = 0.2, P = 0.05, for a two‐tailed unpaired t ‐test), on the basis of a previous study . Those authors compared i.m.y.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Após a publicação de relatos de óbito materno advindo da utilização inadequada da ocitocina 38 , os autores observaram uma mudança na conduta clínica desses anestesiologistas, já que a partir de então apenas 23% mantinham a conduta anterior 41 . Em relação à via de administração, apesar da via intramiometral promover contratilidade uterina eficiente como a via venosa, ela determina maiores alterações hemodinâ-micas (hipotensão arterial e taquicardia) o que pode ser prejudicial em pacientes com baixa reserva cardíaca ou hipovolêmicas 42 . A ocitocina não é o único uterotônico disponível, porém a restrição aos demais agentes ocorre devido aos efeitos colaterais que eles determinam.…”
Section: Utilização Na Prática Clínica Do Anestesiologista Em Cesarianasunclassified
“…After reports of maternal death due to the inadequate use of this drug 38 , the authors observed a change in the clinical conduct of these anesthesiologists, because only 23% of them maintained the older conduct 41 . Regarding the route of administration, although the intramyometrial administration promotes uterine contractility as efficiently as the intravenous route, it causes more hemodynamic changes (hypotension and tachycardia), which can be detrimental in patients with low cardiac reserve or hypovolemic 42 . Oxytocin is not the only uterotonic available; however, there are restrictions to the other agents due to their side effects.…”
Section: Use By Anesthesiologists In Cesarean Sectionsmentioning
confidence: 99%